A framework for Continuous Software Architecture Evaluation - Soares, Rodrigo de Campos (2025)
The increasing complexity and rapid evolution of software systems have made continuous architecture evaluation a crucial aspect of Continuous Software Engineering (CSE). However, existing evaluation approaches remain fragmented, with varying interpretations of continuous evaluation and limited integration into agile and iterative development workflows. This dissertation investigates the role of continuous architecture evaluation in microservice-based systems within the context of CSE, identifying key challenges, trends, and automation opportunities. A systematic mapping study (SMS) analyzes existing research, revealing the need for clearer definitions and structured methodologies. To address this gap, this dissertation proposes a framework, which is composed of a method, a domain-specific language (DSL), and a mechanism that uses service mesh technologies for non-intrusive architectural monitoring. Empirical evaluation through case studies demonstrates the feasibility of the framework, providing real-time feedback and reducing architectural drift. This dissertation then opens several perspectives for future research that should extend automation capabilities, improve architectural assessment in dynamic environments, and explore the long-term impact of continuous evaluation on software evolution.